2016
DOI: 10.1371/journal.pone.0150264
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Affects Oocyte Maturation and Embryo Development in Prepubertal and Adult Cattle

Abstract: High cAMP levels during in vitro maturation (IVM) have been related to improved blastocyst yields. Here, we employed the cAMP/cGMP modulators, forskolin, IBMX, and cilostamide, during IVM to unravel the role of high cAMP in early embryonic development produced from prepubertal and adult bovine oocytes. Oocytes were collected via transvaginal aspiration and randomly assigned to three experimental groups: TCM24 (24h IVM/control), cAMP30 (2h pre-IVM (forskolin-IBMX), 30h IVM-cilostamide), and DMSO30 (Dimethyl Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
0
23
1
1
Order By: Relevance
“…However, reports on bovine oocytes using other cAMP modulators are conflicting, probably due to the differences in protocols and compounds [43,57,58]. In the present study, we did not observe improvement in these parameters but developmental rates using the 10-mM caffeine treatment were similar to the standard control, which prompted us to use this concentration for the vitrification studies.…”
Section: Discussioncontrasting
confidence: 66%
“…However, reports on bovine oocytes using other cAMP modulators are conflicting, probably due to the differences in protocols and compounds [43,57,58]. In the present study, we did not observe improvement in these parameters but developmental rates using the 10-mM caffeine treatment were similar to the standard control, which prompted us to use this concentration for the vitrification studies.…”
Section: Discussioncontrasting
confidence: 66%
“…The accumulation of transcripts during oocyte growth occurs during follicle recruitment, it is thus likely affected by the different hormonal status encountered during initial or cyclic recruitment. In accordance, abundant literature sustains the cytoplasmic immaturity of prepubertal oocytes in terms of abundance of specific transcripts (Bebbere et al, ; Bernal‐Ulloa et al, ; Leoni et al, ; Masala et al, ; Oropeza, Wrenzycki, Herrmann, Hadeler, & Niemann, ).…”
Section: Introductionmentioning
confidence: 55%
“…Studies in ruminants are conflicting as to whether DNA methylation is different between pre-and postpubertal animals. Using limiting dilution bisulfite sequencing, Diederich et al (2012) found that DNA methylation levels at repeat sequences were not different between groups, a finding also reported by Bernal-Ulloa et al (2016) but in contrast with findings in the sheep, in which oocytes from young females had reduced levels of immuoreactive global DNA methylation (Ptak et al 2006). More extensive work using next-generation sequencing would perhaps need to be done in order to identify whether there are specific loci that are not properly methylated in oocytes of prepubertal compared with adult females.…”
Section: The Oocytementioning
confidence: 73%